Improving service quality in highway passenger transportation: a case study using quality function deployment - Pakdil, Fatma; Kurtulmuşoğlu, Feride Bahar (European Journal of Transport and Infrastructure Research, 2014)
The highly competitive market conditions in the passenger transportation industry pressure service provider firms to adopt an attitude of customer-oriented service quality. Even though the service quality of passenger transportation has been a concern in the literature, how the service quality of highway passenger transportation systems could be improved using a systematic approach has not been investigated. Using Quality Function Deployment (QFD), this is the first attempt to improve the quality of highway passenger transportation services. The analysis reveals that the passengers’ most important expectations are employees’ empathetic approach toward customers, technical specifications of buses, error-free services, and competent employees. Additionally, the most important technical requirements are employee-oriented technical requirements, technical specifications of buses, and error-free services in highway passenger transportation.